Amplifying the effects of adding extra players during association football game-based scenarios. - Diogo Coutinho; Bruno Gonçalves; Hugo Folgado; Bruno Travassos; Sara Santos; Jaime Sampaio (PLoS ONE, 2022)
This study aimed to compare under-18 association football players' performance (age = 17.7±1.0 years; playing experience = 9.0 ± 3.2 years) when manipulating the number of teammates and opponents during football game-based practices. Time-motion, individual and tactical-related variables were monitored when manipulating conditions with different number of teammates and opponents (11vs11, No-Sup, No-Inf; 11vs12, Low-Sup, Low-Inf; 11vs13, Mod-Sup, Mod-Inf; and 11vs14, High-Sup, High-Inf). Results showed that adding teammates promoted increases in the longitudinal synchronization from No-Sup to Mod-Sup (Cohen's d with 95% of confidence intervals: 0.25 [0.12; 0.39]; p < .001) and High-Sup (0.61 [0.41; 0.82]; p < .001), while decreases in the distance to the nearest teammate, both in the offensive and defensive phases (p < .001 and p = .005, respectively). In addition, it was observed lower distance covered while running when playing in High-Sup compared to No-Sup (0.30 [-0.01; 0.61]; p = .002) during the defensive phase. Attacking in numerical inferiority promoted a higher variability in the distance to the nearest teammate from No-Inf to High-Inf (0.83 [0.27; 1.38]; p = .044), while decreasing the physical demands, specifically distance covered while running (-0.49 [-0.99; 0.01]; p = .039). In turn, defending, mainly in high-inferiority, increased the total distance covered compared to No-Inf (0.61 [0.30; 0.91]; p < .001) and led to a decrease in the distance to the nearest teammate (-0.90 [-1.35; -0.44]; p = .002). Overall, coaches may manipulate the number of teammates and opponents to promote distinct effects at the level of cooperation and opposition dynamical interactions.